The growth-stimulatory effect of simian virus 40 T antigen requires the interaction of insulinlike growth factor 1 with its receptor. - Porcu, P (1992)
We have used a plasmid expressing a temperature-sensitive (ts) mutant of simian virus 40 (SV40) T antigen, stably transfected into 3T3 cells, to study the role of insulinlike growth factor 1 (IGF-1) and its receptor in T-antigen-mediated growth. While 3T3 cells do not grow in serum-free medium, in 1% serum, or with the sole addition of either platelet-derived growth factor (PDGF) or IGF-1, cells expressing the tsA T antigen (BALB 58 cells) grow at 34 degrees C in either PDGF or 1% serum but not in IGF-1. At the restrictive temperature (39.6 degrees C), these cells can only grow in 10% serum. We show that BALB 58 cells, at 34 degrees C, have a markedly increased expression of IGF-1 and IGF-1 mRNA and that their growth in 1% serum (at 34 degrees C) is inhibited by an antisense oligodeoxynucleotide to the IGF-1 receptor RNA. When this tsA plasmid is stably transfected into cells constitutively overexpressing the human IGF-1 receptor cDNA, the resulting cell lines show a constitutively phosphorylated IGF-1 receptor and grow in serum-free medium at 34 degrees C (but not at 39.6 degrees C). A functional SV40 T antigen also increases the expression of a plasmid in which the reporter luciferase gene is under the control of a rat IGF-1 promoter. We conclude (i) that the SV40 T antigen induces the expression of IGF-1 and IGF-1 mRNA, at least in part by a transcriptional mechanism, thus altering the growth factors requirements, and (ii) that, in BALB/c3t3 cells, the SV40 T antigen necessitates a functional IGF-1 receptor for its growth-stimulating effect in low serum (or PDGF).